Design Study of Long Life Pb-Bi Cooled Reactors With Natural Uranium as Fuel Cycle Input Using Radial Fuel Shuffling Strategy - Rida Siti NM; Zaki Su'ud (Institut Teknologi Bandung, 2007)
Conceptual design study of Pb-Bi cooled fast reactors which fuel cycle need only natural uranium input has been performed. In this design the reactor cores are subdivided into several parts with the same volume. The region with natural uranium is put in the central core while the outer region is arranged with increasing plutonium content. However, in some cases the region with natural uranium content can be put in the most outer part of the core. The arrangement of the plutonium content considers the criteria that the fuel in the certain part must be fit for fresh fuel in the next higher enrichment region. Therefore at the end of a long life operation we just need to supply natural uranium fuel to the blanket region and move other regions properly to the next regions. As an example, using SRAC and FI-ITB CHI code system we obtained a core with 15-20 years life time per sub cycle.